Recombinant Human Nerve Growth Factor (Cenegermin)–Driven Corneal Wound Healing Process: An Evidence-Based Analysis - Bonzano, Chiara; Olivari, Sara; Cutolo, Carlo Alberto; Macrì, Angelo; Sindaco, Daniele; Borroni, Davide; Bonzano, Elisabetta; Traverso, Carlo Enrico (Frontiers in Pharmacology, 2022)
Purpose. To evaluate anterior-segment optical coherence tomography(AS-OCT) to detect the wound healing process as per monitoring the effectiveness of cenegermin to treat moderate-to-severe neurotrophic keratitis (NK). Methods. A retrospective chart review was realized to identify patients treated with cenegermin at Clinica Oculistica, University of Genoa. All patients underwent careful examinations at baseline, and follow-up visits. AS-OCT scans centered on the minimum corneal thickness(CT) area were always performed. We compared findings of the AS-OCT with the findings from the slit-lamp examination. Linear regression analysis was used to evaluate factors associated with corneal healing. A further analysis, including a control group treated with 50% autologous serum(AS), was done to investigate and compare the efficacy of cenegermin. Results. Data from sixteen eyes were involved. The average patients' age was 60.9±21.1 years; Five(31.2%) experienced persistent epithelial defect(PED), eleven eyes(68.8%), had a neurotrophic corneal ulcer(NCU). The average re-epithelialization time was 3.9±0.5weeks in the cenegermin group versus 5.9±1.9weeks in the AS group (p<0.01). The AS‐OCT scans revealed an average CT at the thinnest point of 276,3±74,1μm before treatment with an average increase of 176,5±60,3μm at the end of the cenegermin treatment (B=-0.15; p=0.035). The AS-OCT percentage increase in cornea thickness between the two groups was statistically significant (p<0.02). Conclusion. Understanding the cascade of events involved in the NGF-driven corneal wound healing process is clinically meaningful for the clinician. AS-OCT is an effective tool for systematic anterior-segment imaging. The detailed front-to-back layered cornea structure provided allows quantitative analysis and monitoring of the healing process.